THE INFLUENCE OF INTEGRATED GUID INQUIRY LEARNING MODEL TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE CONCEPT ORGANIZATIONAL SYSTEMS OF LIVING THINGS ON METACOGNITIVE SKILLS AND CRITICAL THINKING ABILITY OF STUDENTS JUNIOR HIGH SCHOOL (SMP) BURU - Nurjani, Siti; Awan, Ali; Wael, Syahran (Universitas Pattimura, 2022)
The guided inquiry learning model integrated with Technological Pedagogical Content Knowledge is a combination of learning models and approaches that utilize technology in the learning process. This study aims to improve students metacognitive skills and critical thinking skills. The material taught in this study is the system of living organizations (cells). This research was conducted in February 2021 in Buru District, Maluku Province. This research was conducted in three schools namely SMP Negeri 5 Buru, SMP Negeri 9 Buru and SMP Negeri 16 Buru, by using a quasi-experimental design type. The populations of this study were VII.a and VII.b at SMP Negeri 5 Buru, SMP Negeri 9 Buru and SMP Negeri 16 Buru, each with a total of 66 students. Data analysis used the Non-Parametric test with the Chi-Square test. The results of this study indicate that, in the metacognitive study there was no effect on SMP Negeri 5 Buru experimental and control classes and experimental class SMP Negeri 9 Buru with a sig > 0.05, while in the control class SMP Negeri 9 Buru and experimental and control classes at SMP Negeri 16 Buru the sig <0.05 it can be concluded that it has an effect. On critical thinking skills at SMP Negeri 5 Buru, SMP Negeri 9 Buru and at SMP Negeri 16 Buru in the experimental and control class the value is sig <0.05. Based on these data, it can be concluded that there is an influence of the guided inquiry learning model integrated with Technological Pedagogical Content Knowledge on students' critical thinking skills.